Large hemangiopericytoma of the shoulder: A case report - Andrić, Kristina; Stanković, Vesna; Spasić, Marko; Rakić, Vesna; Vulović, Dejan (Vojnosanitetski pregled, 2022)
Introduction. Hemangiopericytoma is a rare tumour derived from the pericytes, contractile spindle cells that surround the capillaries and postcapillary venules. The tumour is found equally among males and females. Case report. We reported a case of a 63-year-old female who presented a giant painful mass on her right shoulder that occurred one year before admission. Limited range of motion and a sense of tingling along the affected arm was present also. An irregular, oval-shaped mass, dark red in colour, with signs of necrosis, was 14 cm in maximum diameter. Routine laboratory analysis showed results within the range of referenced values. Lung X-ray and ultrasonographic examination of the abdomen showed no signs of secondary tumour deposits, and no osteomuscular lesions in the affected region. Ultrasonographic examination of the neck and right axillary region showed no signs of regional metastases. The surgical excision of the entire tumour was performed, with the associated subcutaneous tissue and a part of fascia underneath. Results of the histopathological analysis confirmed the diagnosis of hemangiopericytoma. The specimen showed no signs or elements of the neoplastic tissue on the edges of the resection lines. Three years after the operation, there were no signs of tumour relapses, regional or systemic metastases. Conclusion. Considering that there are no official clinical guides and protocols for hemangiopericytoma management, as well as the occurrence of cutaneous and subcutaneous hemangiopericytomas is exceptionally rare, more extensive research in this field and more described cases are needed to gain a better understanding of the issue.